0867 Sleep Duration and Hypertension among >700, 000 Adults by Age and Sex: A Report of the National Healthy Sleep Awareness Project. (27th April 2018) - Grandner, M; Mullington, J; Hashmi, S; Redeker, N; Watson, N; Morgenthaler, T
Abstract: Introduction: The present study evaluated the cross-sectional relationship between sleep duration and hypertension in a large, nationally-representative dataset that spans 10 years. This analysis may provide detailed information with high resolution about how sleep duration is related to hypertension and how this differs by demographic groups. Methods: Data were aggregated from the 2013 Behavioral Risk Factor Surveillance System (BRFSS) (N=433, 386) and the combined 2007–2016 National Health Interview Surveys (NHIS) (N=295, 331). These data were collected by the CDC from nationally-representative samples. Surveys were combined and survey-specific weights were used in all analyses. Sleep duration was assessed with the item, "On average, how many hours of sleep do you get in a 24-hour period?" in both surveys. Hypertension was assessed as self-reported history. Covariates were assessed identically in both datasets and included, age (in 5-year groupings), sex, race/ethnicity, and employment status. Results: In adjusted analyses, compared to 7hrs, increased risk of hypertension was seen among those sleeping ≤4hrs (OR=1.86, p<0.0005), 5hrs (OR=1.56, p<0.0005), 6hrs (OR=1.27, p<0.0005), 9hrs (OR=1.19, p<0.0005), and ≥10hrs (OR=1.41, p<0.0005). When stratified by age, sex, and race/ethnicity groups, short sleep was associated with increased risk for all age groups <70y, and long sleep (≥10hrs only) was associated with risk for all except <24y and >74y. Findings for short sleep were relatively consistent across all race/ethnicities, although findings for long sleep were less pronounced among Black/African-American and Other/Multiracial groups. A significant 3-way sleep-by-age-by-sex interaction (p<0.0005) suggests that the relationship depends on both age and sex. For both men and women, the odds ratio of having hypertension associated with short sleep decreases with increasing age, but there is a higher association between short sleep and hypertension for women, throughout the adult lifespan. Conclusion: Both short and long sleep duration are associated with increased hypertension risk, across most age groups. The influence of covariates is stronger upon long sleep relationships. Relationships with short sleep were stronger among younger adults and women. Support (If Any): The National Healthy Sleep Awareness Project is supported by the CDC.